Avulsion fracture of the anterior superior iliac crest following autograft for anterior lumbar fusion: case report and literature review - Ge, Chao-Yuan; Dong, Liang; Xu, Zheng-Wei; Yang, Wen-Long; Qian, Li-Xiong; Yang, Xiao-Wei; Hao, Ding-Jun (Frontiers in Surgery, 2024)
Avulsion fracture of the anterior superior iliac crest (ASIC) following autogenous bone grafting for anterior lumbar fusion (ALF) is an extremely rare complication. We describe a very rare case of avulsion fracture of the ASIC following autograft for ALF in a revision surgery for treating lumbar tuberculosis. A 68-year-old woman with lumbar tuberculosis underwent posterior debridement and posterior iliac crest bone graft fusion; however, her lumbar tuberculosis recurred 9 months after surgery. She then underwent a lumbar revision surgery, including removal of the posterior instrumentation and debridement, followed by anterior L2 corpectomy, debridement, anterior left iliac crest bone graft fusion, and internal fixation. When walking for the first time on postoperative day 3, she experienced a sharp, sudden-onset pain in the anterior iliac crest harvest area. X-ray revealed an avulsion fracture of the ASIC. Considering her failure to respond to conservative treatment for one week and large displacement of the fracture ends, an open reduction and internal fixation surgery was scheduled. Her pain symptoms were significantly relieved after the operation.Although rare, fracture of the ASIC following autograft for ALF should not be ignored. Fracture of 2 the ASIC is usually treated conservatively. Additional surgical treatment is required only when intractable pain fails to respond to conservative treatment or when there is a large displacement of fracture ends that are not expected to heal spontaneously.